Analisis Akurasi Penerjemahan Bahasa Arab Lewat Fitur Auto Translate pada Aplikasi Twitter - Kisno Umbar; Aisyah Adilah; Rahma Raihana Romadona; Muhammad Rafli (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2023)
This study aims to describe the errors and accuracy of translation on automatic translation machines on the Twitter application and to find out the automatic translation procedures carried out on the Twitter application. The method used by the authors in this study is a qualitative research with a descriptive approach. The data obtained in this study was carried out by observation or indirect observation of uploads contained in the Twitter application where there were irregularities in the translation. Researchers utilize sources that come from Twitter users who use Arabic in their "tweets". This study also used a simple random sampling technique (simple random sampling). The results obtained in this study indicate that there are deviations in meaning or translations made on the automatic translation machine on the Twitter application which causes the translation results to be incompatible between the Source Language (SL), namely Arabic to the Target Language (TL), namely Indonesian. The existence of deviations or word errors in the translation results carried out in the automatic translation of the Twitter application is due to differences in sentence structure arrangement between SL and TL and there is no equivalent word.